Hubungan Paritas Dengan Tingkat Kecemasan Ibu Hamil Trimester III Dalam Menghadapi Persalinan - Triatmi Andri Yanuarini; Dwi Estuning Rahayu; Hanna Salehtra Hardiati (coba, 2013)
At each stage of pregnancy , pregnant women will experience different psychological processes . In the third trimester approaching delivery day there will be a new turmoil to deal with childbirth . With the approach of the time of delivery , a mother haunted by face anxiety the birth process . Birth experience is different from one woman to another , as well as between the first delivery with the next labor in women at the same or different women. Psychological changes dealing labor influenced by several factors , one of which is a factor that can be determined prior experience of parity . The purpose of this study was to determine is there a relationship between parity with the level of anxiety in the third trimester pregnant women facing childbirth . This study uses cross-sectional correlation research design . The sample used by 30 respondents third trimester pregnant women with quota sampling technique . While the variables studied were parity using parity data collection table and anxiety levels using a questionnaire ( Scale HARS ) . The data were analyzed using the Spearman correlation test with 95% confidence intervals . From the results of the study found the majority of respondents nullipara status ( 43.33 % ) and their level of anxiety experienced third trimester pregnant women were mostly anxiety ( 43.33 % ) . After analysis of data by using the Spearman correlation test results obtained by the relationship between parity with the level of anxiety in the third trimester pregnant women facing childbirth.